2015
DOI: 10.1016/j.biosystemseng.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Decision making models embedded into a web-based tool for assessing pest infestation risk

Abstract: Current practices in agricultural management involve the application of rules and techniques to ensure high quality and environmentally friendly production. Based on their experience, agricultural technicians and farmers make critical decisions affecting crop growth while considering several interwoven agricultural, technological, environmental, legal and economic factors. In this context, decision support systems and the knowledge models that support them, enable the incorporation of valuable experience into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…We were able to develop action thresholds between 2012 and 2017. A risk-aversion gradient approach was taken [61,62]. A risk-based action threshold is appropriate given the different production systems that exist in Maine for wild blueberry and given that markets range from local fresh market roadside sales, to the export of frozen berries to foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to develop action thresholds between 2012 and 2017. A risk-aversion gradient approach was taken [61,62]. A risk-based action threshold is appropriate given the different production systems that exist in Maine for wild blueberry and given that markets range from local fresh market roadside sales, to the export of frozen berries to foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…20 Current practices in agricultural management involve the application of rules and techniques to ensure high quality and environmentally friendly production. 21 The results in Table 5 showed that 40% of the respondents their source of ploughing information were services centres, 35% of them got from others farmers and only 25% from extension. For source of preparing land information 51% of the respondents their source were other farmers, 26% of them accessed from extension and only 23% got information from service centres.…”
Section: Results Of Descriptive Analysismentioning
confidence: 98%
“…Pest control is a vital process in the agricultural business, as pests and diseases can lead to important economic and ecological losses [88]. A number of DSSs have focused on providing support for farmers to identifying and treating ( [52,31]) a particular pest (see Figure 7).…”
Section: Pest and Disease Controlmentioning
confidence: 99%